Will China Take over the World in the Middle of the 21st Century? (Economic and Political Thought, 2023)
The aim of the article is to try to answer the question posed in its title, namely: will China rule the world in the middle of the 21st century? The main hypothesis is that today it is impossible to give an unambiguous answer to such a question, taking into account the distant perspective, i.e. the middle of the 21st century and the enormous dynamics of changes that are currently taking place in the world. Another hypothesis is that the rivalry between China and the United States for global hegemony does not take place in a geoeconomic and geostrategic vacuum, and that its course and effects are and will be significantly influenced by other subjects of international law and international relations, including regional powers, especially those belonging to the so-called BRICS group, led by Russia, as well as the European Union and NATO. In addition, the struggle of China and the US for world leadership will also be influenced by processes such as international integration/disintegration and globalisation/deglobalisation, as well as the growing populism, nationalism and isolationism in the foreign policy of many countries, including in China and the US. In the article, I pose a few questions, adequate to the research hypotheses put forward, including what political, international, economic, technological, and military/strategic assets does China have at its disposal to successfully compete with the United States in these areas? Will the United States accept the prospect of losing world leadership? Is it still possible for China and the United States to cooperate peacefully and for them to jointly lead the world within the framework of the so-called Chimerica, i.e. the bipolar international order, the theoretical concepts of which were considered in the science of international relations at the turn of the 20th and 21st centuries by many American researchers and experts? In addition, Furthermore, I ask whether the new international order that will eventually emerge from the current international stagnation will be democratic and peaceful, and will it be a unipolar, bipolar or multipolar order?
Keywords: China, United States, East, West, rivalry, confrontation, hegemony world, 21st century